Hereditary haemorrhagic telangiectasia, rendu-osler-weber - Serra, Marcelo M. (Revista del Hospital Italiano de Buenos Aires, 2014)
The Hereditary Hemorrhagic Telangiectasia (HHT) known as Rendu-Osler-Weber Syndrome, is an inherited vascular dysplasia characterized by the presence of mucocutaneous telangiectases, frequent epistaxis and arteriovenous malformations (AVMs) in organs such as the brain, lung, liver and digestive tract. Its global prevalence is 1/5000 -1/8000. It is considered a rare disease, though an important underdiagnosis is suspected. The HHT affects the quality of life significantly and multiple complications and comorbidities are associated. It’s caused by mutations in the TGFβ receptor and signaling proteins mainly in the endothelium, affecting the normal angiogenic modulation. The diagnosis can be made based on the Curaçao clinical criteria and or genetic test which are especially useful in asymptomatic children. The epistaxis and gastrointestinal bleeding frequently lead to iron deficiency anemia and might be life-threatening, too. The ischemic stroke, brain and spinal abscesses are severe complications secondary to the arteriovenous pulmonary fistulae shunt, which have to be closed through embolotherapy. A hemorrhagic stroke is another severe complications from HHT since the brain and spinal cord may harbor AVMs. The liver is usually affected but hepatic clinical problems occur in a few patients who suffer from secondary pulmonary hypertension, portal hypertension or ischemic necrosis in the biliary tree. There are many therapeutic strategies to prevent serious complications and improve the quality of life of the patients suffering from this rare disease